Evaluation of new irish potato (solanum tuberosum l.) varieties for yield potential in Zimbabwe - Mpemba, Tapiwa Ronald (Midlands State University, 2017)
Irish potato (Solanum tuberosum L.) is an important crop in Zimbabwe due to its nutritional and economic worth. The upgrading of its status to a strategic food crop by the government in 2012 has created the need for research to increase production, increase germplasm and diversify staple food crops. A study to investigate the yield potential of new Irish potato varieties was carried out at the Scientific Industrial Research and Development Centre between June and November 2015. Aim of the study was to evaluate new varieties to introduced and released in Zimbabwe. The varieties BRI1, BRI2, BRI3, BRI4, BRI5, BRI6 and BRI7 were grown with the controls being locally released varieties Amethyst and BP1 which are long and short season varieties respectively. The experiment was laid out in a randomised complete block design with 9 treatments and slope as the blocking factor. Analysis of variance was done using Genstat 14th edition. Data on yield, number of days to 50 % flowering and number of days to 95 % maturity was recorded. Analysis of variance showed that there was a significant difference (P<0.05) in the yield of potatoes, number of days to 50% flowering and number of days to 95% physiological maturity due to variety. BRI6 and BRI3 achieved the highest yields of 69.63 and 58.89 t/ha respectively. BP1 and BRI7 had the lowest yields of 13.22 and 9.89 t/ha respectively. Amethyst and BRI7 took the highest number of days to 50 % flowering of 30.33 and 29 respectively. BRI6 and BRI1 took the least number of days to 50 % flowering of 17 and 16.67 respectively. BRI7 and BRI5 took the longest number of days to reach maturity with 139.3 and 136.7 respectively. BRI1 and BP1 took the least number of days to maturity with 100 days each. The research concluded that the new varieties had a higher yield potential. BRI6 had the highest yield followed by BRI3, BRI2, BRI2, BRI4, BRI5, Amethyst, BP1 and BRI1. The varieties BRI7, BRI5, BRI3, BRI4, BRI2, BRI6 and Amethyst are long season varieties while BRI1 and BP1 are short season varieties. A multi locational trial is required to determine the yield potential of the varieties in the different farming regions of the country. The varieties should also be screened for drought tolerance as well as pest and disease resistance.